2004
DOI: 10.1017/s0033291704002454
|View full text |Cite
|
Sign up to set email alerts
|

Self-monitoring in patients with schizophrenia

Abstract: These results support the claim that a failure of self-monitoring may underlie the core symptoms of schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
1
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(69 citation statements)
references
References 31 publications
6
58
1
4
Order By: Relevance
“…In a situation when there is no difference, action or thought is classified as produced by the self. In such patients, this process may be impaired, the consequence of which is inappropriate assignment of the origin of actions or thoughts [22].…”
Section: Discussionmentioning
confidence: 99%
“…In a situation when there is no difference, action or thought is classified as produced by the self. In such patients, this process may be impaired, the consequence of which is inappropriate assignment of the origin of actions or thoughts [22].…”
Section: Discussionmentioning
confidence: 99%
“…It is also supported by evidence that this awareness is absent or delayed when the brain areas responsible for these predictions are temporarily disturbed using transcranial magnetic stimulation methods or are damaged (Haggard and Magno, 1999;Desmurget & Sirigu, 2009). Evidence for claim (2) -that the sense of agency also depends on the congruence between predictions and sensory reafferences -comes from studies showing that gradually disrupting the consequences of actions by introducing temporal delays or spatial inconsistencies gradually reduces the sense of agency (Fourneret & Jeannerod, 1998;Knoblich, Stottmeister, & Kircher, 2004;Leube et al, 2003;Sato & Yasuda, 2005;Sato, 2009). …”
Section: The Sense Of Agency For Individual Actions: Sources and Mechmentioning
confidence: 96%
“…MP and MA as tested in study 1 may be influenced in the highly trained processing of upright bodies, and it may not transfer to less trained postures such as inverted bodies that have been shown to decrease performance in the perception of body postures (Reed et al, 2003) and biological motion (Cutting, Moore, & Morrison, 1988), as well as self-attribution of arm actions Knoblich, Stottmeister, & Kircher, 2004). Moreover, performance may also be dependent on the perspective (David et al, 2006;Vogeley & Fink, 2003) or direction from which the virtual body is shown as MA during goal-directed arm movements has been shown to decrease if the direction of the virtual arm movement is rotated by 180 • (van den Bos & Jeannerod, 2002).…”
Section: Studymentioning
confidence: 98%